Marine benthic algae from Uruçuca, Bahia, Brazil - Nunes, José Marcos de Castro; dos Santos, Ana Cristina Caribé; Lyra, Goia de Mattos; Minervino-Netto, Augusto; Pedreira, Emmanuele Silva (Acta Botanica Malacitana, 2001)
Algas marinas bentónicas del municipio de Urupica, Bahia, Brasil .